Analyses of Pepper Cinnamoyl-CoA Reductase Gene Family and Cloning of CcCCR1/2 and Their Function Identification in the Formation of Pungency - Dan Wu; Miao Ni; Xin Lei; Liping Zhang; Wei Zhang; Huangying Shu; Zhiwei Wang; Jie Zhu; Shanhan Cheng; Pingwu Liu; Honghao Lv; Limei Yang (Horticulturae, 2022)
Cinnamoyl-CoA reductases (CCR) have a possible role in pungency formation of pepper because they can convert feruloyl-CoA, sinapoyl-CoA, and p-coumaroyl-CoA into lignin, which are also competitive precursors of capsaicin biosynthesis in phenylpropanoid metabolism. In this study, genome-wide CCR gene family, exon–intron structures, sequence homology, phylogenetic characterization, and promoters were analyzed in pepper. Two CCR genes were cloned from Capsicum chinense, their enzymic kinetic parameters and regulatory function were identified by heterologous expression, ectopic expression, and VIGS. In total, 38 genes were found as predicted CCRs or CCR-like proteins and were composed of 2–10 exons. The promoters of pepper CCRs contained growth, stress, hormone, and light-response elements. The affinity and catalytic efficiency of CcCCR1/2 to feruolyl-CoA was the highest. The analysis of metabolic substances showed that capsaicin content was negatively correlated with lignin and positively correlated with flavonoids. The highest expression of CcCCR1 was found in stems, the higher expression of CcCCR2 was found in stem and early fruit than other organs. CCR1, 2 had certain effects on capsaicin content by regulating related enzyme activity, CCR2 played a more important role in regulating pungency formation. Our results clarify the competitive mechanism between lignin and capsaicin biosynthesis and provide an explanation for spice regulation.